2013
DOI: 10.1371/journal.pone.0078289
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Randomized Clinical Trial of Candidate Human Immunodeficiency Virus type 1 Vaccine MVA.HIVA Administered to Gambian Infants

Abstract: BackgroundA vaccine to decrease transmission of human immunodeficiency virus type 1 (HIV-1) during breast-feeding would complement efforts to eliminate infant HIV-1 infection by antiretroviral therapy. Relative to adults, infants have distinct immune development, potentially high-risk of transmission when exposed to HIV-1 and rapid progression to AIDS when infected. To date, there have been only three published HIV-1 vaccine trials in infants.Trial DesignWe conducted a randomized phase I clinical trial PedVacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
13
1
Order By: Relevance
“…Given the differences between the H-2 d and HLA major histocompatibility complex molecules, only some peptides immunogenic in the BALB/c mouse are also presented by the human HLAs. Thus, peptide H is unusual in that it has four anchor residues for H-2D d ( 30 , 31 ) and displays “promiscuous” binding to four different H-2D d , H-2D p , H-2 u , and H-2 q murine determinants ( 32 ) as well as human HLA-A2 ( 33 ), although in our hands, in human volunteers ( 16 , 34 43 ) or HLA-A2-transgenic HHD mice (unpublished data), such responses were never detected for either the HIVA ( 20 ) or the HIVconsv ( 9 ) immunogens. No responses were detected in 23 human recipients of the HIVconsv vaccine to peptide 42 or 112, while T cells were induced to peptides 151 and 164 ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the differences between the H-2 d and HLA major histocompatibility complex molecules, only some peptides immunogenic in the BALB/c mouse are also presented by the human HLAs. Thus, peptide H is unusual in that it has four anchor residues for H-2D d ( 30 , 31 ) and displays “promiscuous” binding to four different H-2D d , H-2D p , H-2 u , and H-2 q murine determinants ( 32 ) as well as human HLA-A2 ( 33 ), although in our hands, in human volunteers ( 16 , 34 43 ) or HLA-A2-transgenic HHD mice (unpublished data), such responses were never detected for either the HIVA ( 20 ) or the HIVconsv ( 9 ) immunogens. No responses were detected in 23 human recipients of the HIVconsv vaccine to peptide 42 or 112, while T cells were induced to peptides 151 and 164 ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 testing was performed using HIV-1 DNA PCR at birth, 6, 10, 14 and 20 weeks; HIV-1 viral load at 19, 28, 36 and 48 weeks and HIV-ELISA at 48 weeks. Peripheral blood mononuclear cells (PBMC) were isolated and used for interferon (IFN)-γ ELISPOT assays or frozen [23] .…”
Section: Methodsmentioning
confidence: 99%
“…Fresh ex vivo and cultured IFN-γ ELISPOT assays were carried out as previously described [23] . An assay failed quality control if the mean background was >20 spot-forming units (SFU)/well (>100 SFU/10 6 PBMC) or mean phytohemagglutinine response was <30 SFU/well (<150 SFU/10 6 PBMC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No severe adverse events occurred during the trial, and the vaccine did not interfere with antibody induction to the standard childhood vaccines. However, only 9% of vaccinated infants demonstrated an HIV-1-specific T cell response [65]. The most promising vaccine study so far, a trial of ALVAC-HIV vCP 1521 among adults in Thailand that incorporated boosting with 2 recombinant envelope proteins, found that the vaccine had 31% efficacy (95% CI: 1.1–51.1%; P = .04) [66].…”
Section: Immunoprophylaxismentioning
confidence: 99%